Women Managers Moving On : What Might Influence Their Career Advancement and Satisfaction in the Indian Hotel Industry? - Patwardhan, Vidya; Mayya, Sureshramana; Joshi, Harish (Prabandhan: Indian Journal of Management, 2018)
We examined the relationship between personal strategies, organizational strategies, career experiences, and objective and subjective indicators of career advancement (promotion rate and job and career satisfaction) of 344 women managers of Indian five-star hotels. On the basis of literature reviewed and discussions with executive women in hospitality, it was hypothesized that the career advancement is associated with facilitators and constraints (termed as dimensions of mobility pathway), the contextual factors (age, education, marital status, managerial levels, and total service), and personal (by the individual) & organizational strategies (supported by the organization). It was posited that these factors are potentially interrelated. The structural equation modelling results revealed that the personal and organizational strategies did not mediate the relationships. Interestingly, the most debated issue of 'glass ceiling' had not impacted their job and career satisfaction. Nonetheless, the presence of organizational support systems had an impact on work outcomes, indicating that women were satisfied with job and career. Together, these findings indicated that women managers may adjust their feelings of satisfaction to reduce dissonance and remain committed to employment. The results may contribute to identify obstacles and career supports to offer directions to Indian five-star hotels interested in supporting career advancement of women managers.